Association of Local Recurrence with Subsequent Survival in Extremity Soft-Tissue Sarcoma - Lewis, J. J. (Institutional Knowledge at Singapore Management University, 1997)
The aim of this study was to analyze local recurrence in a large cohort of prospectively followed patients with primary extremity soft tissue sarcoma. In particular, we analyzed the correlation of local recurrence with subsequent metastasis and disease-specific survival. Patients and Methods: Patients who underwent treatment for primary extremity soft tissue sarcoma from July 1982 through July 1995 at Memorial Sloan-Kettering Cancer Center were the subject of this study. Local recurrence, distant metastasis, and disease-specific survival were used as end points of the study. The influence of local recurrence on subsequent distant metastasis and disease-specific survival were examined using the Cox proportional hazards model. Results: We treated 911 patients, of whom 297 (33%) developed recurrent disease. Local recurrence occurred in 116 patients (13%), metastasis in 167(18%), and synchronous local recurrence and metastasis in 13 (2%). Of 116 patients who developed local recurrence, 38 subsequently developed metastasis and 34 died of disease. Metastasis after local recurrence was predicted in patients with initial high-grade (P = .005; risk = 3.5) or deep (P = .02; risk = 2.9) tumors. Tumor mortality after local recurrence was predicted in patients with initial high-grade (P = .007; risk = 3.7) or large (> 5 cm; P = .01; risk = 3.2) primary tumors. Discussion: These findings suggest that there is a strong association of local recurrence with the development of subsequent metastasis and tumor mortality, and that local recurrence is a poor prognostic factor. It would seem prudent to consider patients who develop local recurrence and have high-grade tumors as being at high risk for systemic disease and therefore eligible for investigational adjuvant systemic therapy.